«These are basically lost cases». The prosecution of human trafficking in Madre de Dios, Peru - Tuesta, Diego (2018)
Research on the prosecution of human trafficking is scarce in South America. This paper provides evidence of criminal procedures for this offense in Madre de Dios, one of Peru’s emblematic gold mining enclaves. I demonstrate that prosecutors’ behaviour is shaped by a plurality of actions, which contrasts contemporary scholarship focus on rational choice theory. I also shed light on penal selection patterns, or why prosecutors prioritize some cases instead of others. Although discretion is certainly a key aspect, I find that other variables—such as the cultural organization within justice practitioners—play an important role to explain the aforementioned behaviour.